The snowy day. - Keats, Ezra Jack. (New York, Scholastic, 1962)
The adventures of a little boy in the city on a very snowy day.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Caldecott 1967 Medal Winner
3.2
K-3
Keywords: Snow -- Fiction; Afro-Americans -- Fiction; Snow -- Fiction